The empowerment of health cadres in assisting pregnant women during the covid-19 pandemic - Ana Majdawati; Ivanna Beru Brahmana (Universitas Ahmad Dahlan, 2022)
The questionnaire results on pregnant women at the Primary Health Service of Jetis II in Bantul, Yogyakarta, show that a woman contracts Covid-19. Meanwhile, other findings are that pregnant women get tired quickly (81.82%), many are not orderly to wear masks (76%), about the effects of Covid on mothers and fetuses (over 50%). Health cadres have not been optimal in assisting pregnant women in preventive and follow-up efforts. This community service program aims to empower health cadres in helping pregnant women during the pandemic by increasing knowledge